Bioengineered miR-328-3p modulates GLUT1-mediated glucose uptake and metabolism to exert synergistic antiproliferative effects with chemotherapeutics - Wanrong Yi; Mei-Juan Tu; Zhenzhen Liu; Chao Zhang; Neelu Batra; Ai-Xi Yu; Ai-Ming Yu (Elsevier, 2020)
MicroRNAs (miRNAs or miRs) are small noncoding RNAs derived from genome to control target gene expression. Recently we have developed a novel platform permitting high-yield production of bioengineered miRNA agents (BERA). This study is to produce and utilize novel fully-humanized BERA/miR-328-3p molecule (hBERA/miR-328) to delineate the role of miR-328-3p in controlling nutrient uptake essential for cell metabolism. We first demonstrated successful high-level expression of hBERA/miR-328 in bacteria and purification to high degree of homogeneity (>98%). Biologic miR-328-3p prodrug was selectively processed to miR-328-3p to suppress the growth of highly-proliferative human osteosarcoma (OS) cells. Besides glucose transporter protein type 1, gene symbol solute carrier family 2 member 1 (GLUT1/SLC2A1), we identified and verified large neutral amino acid transporter 1, gene symbol solute carrier family 7 member 5 (LAT1/SLC7A5) as a direct target for miR-328-3p. While reduction of LAT1 protein levels by miR-328-3p did not alter homeostasis of amino acids within OS cells, suppression of GLUT1 led to a significantly lower glucose uptake and decline in intracellular levels of glucose and glycolytic metabolite lactate. Moreover, combination treatment with hBERA/miR-328 and cisplatin or doxorubicin exerted a strong synergism in the inhibition of OS cell proliferation. These findings support the utility of novel bioengineered RNA molecules and establish an important role of miR-328-3p in the control of nutrient transport and homeostasis behind cancer metabolism. Key words: Bioengineered RNA, MiR-328, LAT1, GLUT1, Chemosensitivity, Cancer